Plio‐Quaternary Outer Forearc Deformation and Mass Balance of the Southern Costa Rica Convergent Margin. Issue 9 (5th September 2019) - Morell, Kristin D.; Fisher, Donald M.; Bangs, Nathan
Abstract: Identifying the processes that control the rates, magnitudes, and longevity of outer forearc deformation is fundamental to our understanding of how mass is distributed within subduction zone systems. The margin of southern Costa Rica has been the target of numerous onland field studies, geophysical surveys, and the Costa Rica Seismogenesis Project (CRISP) drilling expedition. Despite these extensive data sets, the relative roles that subduction erosion, shortening, and seamount subduction play in shaping the behavior and evolution of the outer forearc remain debated. Here we analyze new and existing geomorphic, geologic, stratigraphic, and geochronologic data sets across the entire forearc‐arc‐backarc system near the Costa Rica Seismogenesis Project transect to test several conceptual models for outer forearc deformation in southern Costa Rica. The results from the compilation agree with a model where recent arcward retreat of the trench (movement of the trench in the direction of the arc) occurs due to underthrusting of the outer forearc beneath the inner forearc, and outer forearc deformation occurs primarily by transient rapid vertical tectonism due to the subduction of bathymetric relief. These results lead to a new conceptual model for Plio‐Quaternary outer forearc deformation in southern Costa Rica that does not require large amounts of net mass loss within the upper plate. Key Points: Trench retreat in southern Costa Rica can be explained by inner forearc shortening Outer forearc vertical deformation occurs primarily due to the subduction of bathymetric relief We present a new model for Plio‐Quaternary deformation that does not require significant upper plate mass loss